2021
DOI: 10.3390/ijms22084278
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs Act as Diagnostic Biomarkers for Bladder Cancer in Urine

Abstract: MicroRNAs (miRNAs) can be secreted into body fluids and have thus been reported as a new type of cancer biomarker. This study aimed to determine whether urinary miRNAs act as noninvasive biomarkers for diagnosing bladder cancer. Small RNA profiles from urine were generated for 10 patients with bladder cancer and 10 healthy controls by using next-generation sequencing. We identified 50 urinary miRNAs that were differentially expressed in bladder cancer compared with controls, comprising 44 upregulated and six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
1
22
0
1
Order By: Relevance
“…In the current study, the signi cantly higher expression levels for people carrying the variant genotypes (CG and GG) of mir146a rs2910164 than those carrying the wile-type CC genotypes provide biological plausibility for the associations of CG and GG genotypes with increased BLCA risks. The ndings are in line with that of Lin and Tsai's previous reports, mentioning that mir146a were signi cantly elevated in the urine of BLCA patients than the normal controls 24 . Although the pilot study is of relatively small sample size, the elevation of mir146a has been also con rmed in The Cancer Genome Atlas database with 19 controls and 416 BLCA cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the signi cantly higher expression levels for people carrying the variant genotypes (CG and GG) of mir146a rs2910164 than those carrying the wile-type CC genotypes provide biological plausibility for the associations of CG and GG genotypes with increased BLCA risks. The ndings are in line with that of Lin and Tsai's previous reports, mentioning that mir146a were signi cantly elevated in the urine of BLCA patients than the normal controls 24 . Although the pilot study is of relatively small sample size, the elevation of mir146a has been also con rmed in The Cancer Genome Atlas database with 19 controls and 416 BLCA cases.…”
Section: Discussionsupporting
confidence: 92%
“…While one came out with negative ndings 22 , the other provided evidence that mir146a rs2910164 may play an important role in BLCA 23 . More recently, Lin and Tsai reported mir196a, in addition to mir146a, was signi cantly increased in its expression level among BLCA patients 24 .…”
Section: Introductionmentioning
confidence: 98%
“…In particular, the loss of endothelial miR-126 might explain the impaired peripheral angiogenic signaling in patients [ 23 ]. In the current special issue, outstanding examples have been provided by Lin and Tsai [ 24 ] and Oto et al [ 25 ] in bladder and renal cell cancer, respectively, and by Salloum-Asfar et al in Autism Spectrum Disorder [ 26 ].…”
mentioning
confidence: 99%
“…Use of NGS to analyze umiRNAs has another advantage, in that researchers can verify their data by referring to published databases such as The Cancer Genome Atlas (TCGA), which generates and analyzes NGS data from the whole genome in various cancer types. Two recent studies explored expression levels of umiRNAs in patients with BCa and, using data from TCGA, validated an overlapping of certain miRNAs with altered expression levels [ 44 , 45 ]. Braicu et al identified five umiRNAs in common between a patient cohort and TCGA data [ 44 ].…”
Section: Diagnostic Utility Of Biomarkers Assessed By Liquid Biopsymentioning
confidence: 99%